The ambivalent partisan how critical loyalty promotes democracy - Lavine, Howard; Johnston, Christopher D.; Steenbergen, Marco R. (New York ; Oxford : Oxford University Press, 2013)
Taking aim at decades of received wisdom, the central claim of this book is that high-quality political judgment hinges less on citizens' cognitive ability than on their willingness to temporarily suspend partisan habits and follow the 'evidence' wherever it leads. This occurs most readily when citizens experience a disjuncture between their stable political 'identities' and their contemporary 'evaluations' of party performance, a state the authors refer to as 'partisan ambivalence'.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Keywords: Party affiliation -- United States; Democracy -- Psychological aspects; Political participation -- United States -- Psychological aspects; Voting -- United States -- Psychological aspects